Implant material and method for manufacturing implant material

The implant material addresses the limitation of insufficient phospholipid support by using electrostatic adsorption with compounds having isoelectric points greater than 7, resulting in enhanced tissue regeneration and reduced inflammation.

JP7618206B2Active Publication Date: 2025-01-21NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2020207430
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-15
Publication Date
2025-01-21
Estimated Expiration
2040-12-15

AI Technical Summary

Technical Problem

Existing implant materials, such as those coated with phospholipids, face limitations in supporting a sufficient amount of phospholipids due to their insolubility in water, which affects their ability to promote tissue repair and regeneration around surgical sites.

Method used

An implant material comprising a base material coated with a layer containing phospholipids and compounds with isoelectric points greater than 7, utilizing electrostatic adsorption to increase the supported phospholipid amount, including glycerophospholipids and proteins like protamine, is developed through a method of alternating immersion in phospholipid and protein/peptide solutions.

Benefits of technology

The implant material effectively supports a higher amount of phospholipids, enhancing tissue regeneration and reducing inflammation, making it suitable for implantation in the body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618206000002
    Figure 0007618206000002
  • Figure 0007618206000003
    Figure 0007618206000003
  • Figure 0007618206000004
    Figure 0007618206000004
Patent Text Reader

Abstract

To provide an implant material having a sufficient amount of phospholipid supported thereon.SOLUTION: An implant material 1 has a substrate 3 and a coating layer 5 for coating the surface of substrate 3. The coating layer 5 contains at least one phospholipid that, when dispersed in water, shows an isoelectric point smaller than 7, and at least one compound selected from the group consisting of proteins and peptides that, when dispersed in water, show an isoelectric point greater than 7.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to implant materials and methods of making implant materials. [Background technology]

[0002] One of the most important things to do in managing patients immediately after surgery is to prevent blood clots and inflammation. Another important thing to do from the time of surgery until discharge is to repair the tissue around the surgical site. If wounds caused by incisions during surgery, sutures, and tissue repair around implants are delayed, patients will have to wait longer to start rehabilitation, and their hospital stay will be longer, which can be a major disadvantage for patients. Tissue regeneration is particularly slow around the jaw. Age also reduces the repair function. Therefore, implant materials that promote tissue repair around wounds generated when an affected area is incised during surgery, suture sites, and implanted components are being studied. For example, Patent Document 1 studies phospholipid-coated implants. Patent Document 1 shows that phosphatidylserine, a phospholipid, is non-thrombotic and anti-inflammatory, and discloses an anti-thrombotic implant material coated with phosphatidylserine. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2003-508129 Summary of the Invention [Problem to be solved by the invention]

[0004] However, the amount of phospholipid supported by the implant material of Patent Document 1 was not necessarily sufficient. That is, since phospholipids are not soluble in water, phospholipids are dissolved in an organic solvent and coated on a base material by a dipping method, but this method has a limit to the amount of phospholipid that can be supported. The present disclosure has been made in view of the above circumstances, and aims to provide an implant material carrying a sufficient amount of phospholipid. The present disclosure can be realized in the following forms. [Means for solving the problem]

[0005] [1] An implant material comprising a substrate and a coating layer that coats a surface of the substrate, The coating layer is At least one kind of phospholipid having an isoelectric point of less than 7 when dispersed in water; At least one compound selected from the group consisting of proteins and peptides having an isoelectric point of more than 7 when dispersed in water; An implant material comprising:

[0006] [2] The implant material according to [1], wherein the phospholipid is a glycerophospholipid.

[0007] [3] The implant material according to [1] or [2], wherein the coating layer contains protamine as the protein.

[0008] [4] The implant material according to any one of [1] to [3], wherein the substrate is made of a metal, a polymer, or a composite thereof.

[0009] [5] A first liquid containing at least one compound selected from the group consisting of proteins and peptides, the compound having an isoelectric point of more than 7 when dispersed in water; A second liquid containing liposomes formed by containing phospholipids, A method for producing an implant material, comprising at least a step of alternately immersing a substrate in the first liquid and the second liquid. Effect of the Invention

[0010] The implant material of the present disclosure contains not only phospholipids in the coating layer, but also at least one compound selected from the group consisting of proteins and peptides, and the amount of phospholipids supported is increased. That is, the coating layer can be made thicker by utilizing the electrostatic adsorption action between the phospholipids and at least one compound selected from the group consisting of proteins and peptides, and therefore the amount of phospholipids supported can be increased. Since at least one compound selected from the group consisting of proteins and peptides has an isoelectric point of more than 7, electrostatic adsorption can be easily utilized and phospholipids can be sufficiently supported. When the phospholipid is a glycerophospholipid, the effect of promoting tissue regeneration is high. When the coating layer contains protamine as a protein, it can sufficiently support phospholipids. When the substrate is made of a metal, a polymer, or a composite thereof, it becomes an implant material useful for implantation in a living body. In the production method of the present disclosure, a sufficient amount of phospholipids can be supported by utilizing electrostatic adsorption between negatively charged liposomes and positively charged proteins or the like. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram showing the estimated structure of an implant material. [Diagram 2] 1 is a graph showing the relationship between the number of cycles and the amount of PSL loaded. [Diagram 3] 1 is a graph showing the relationship between the number of cycles and the amount of the inflammatory cytokine IL-6. [Figure 4] 1 is a graph showing the relationship between cycle number and PSL loading for various substrates. [Diagram 5] 1 is a graph showing the amount of PSL supported when proteins having different isoelectric points are used. [Figure 6] 1 is a graph showing the effect of the amount of PSL carried on the amount of new bone formation. [Figure 7] 1 is a graph showing the effect of the amount of PSL loaded on regenerated muscle mass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. In this specification, when a numerical range is described using "to", the range includes the lower limit and the upper limit unless otherwise specified. For example, the description "10 to 20" includes both the lower limit "10" and the upper limit "20". In other words, "10 to 20" has the same meaning as "10 or more and 20 or less".

[0013] 1. Implant material 1 The implant material 1 includes a base material 3 and a coating layer 5 that coats the surface of the base material 3 . The coating layer 5 contains a phospholipid and at least one compound selected from the group consisting of a protein and a peptide. Figure 1 shows a schematic diagram of an implant material 1. Reference numeral 7 denotes a liposome formed containing a phospholipid, and reference numeral 9 denotes at least one compound selected from the group consisting of a protein and a peptide.

[0014] The substrate 3 is made of a metal, a polymer, a ceramic, or a composite thereof. The metal is not particularly limited. For example, titanium, a titanium alloy, a magnesium alloy, and stainless steel are preferably used as the metal. The polymer is not particularly limited. For example, polyether ether ketone (PEEK), polylactic acid (PLA), polylactic acid-glycolic acid copolymer (PLGA), polytetrafluoroethylene (PTFE), polyethylene terephthalate (PET), collagen, and atelocollagen are preferably used as the polymer. For example, zirconia, alumina, hydroxyapatite, and calcium phosphate-based materials (such as tricalcium phosphate) are preferably used as the ceramic.

[0015] There is no particular limitation on the thickness of the coating layer 5. The thickness of the coating layer 5 can be, for example, 1 μm to 100 μm.

[0016] The phospholipid is not particularly limited as long as it has an isoelectric point of less than 7 when dispersed in water. A suitable example of the phospholipid is glycerophospholipid. The glycerophospholipid is preferably at least one selected from the group consisting of phosphatidylserine, phosphatidic acid, phosphatidylinositol, phosphatidylglycerol, phosphatidylcholine, and phosphatidylethanolamine. Phosphatidylserine, phosphatidic acid, phosphatidylinositol, and phosphatidylglycerol have isoelectric points lower than 7 and can form a coating layer by themselves.

[0017] From the viewpoint of sufficiently forming the coating layer 5 by utilizing electrostatic adsorption, the at least one compound selected from the group consisting of proteins and peptides has an isoelectric point of greater than 7 when dispersed in water. The upper limit of the isoelectric point is 14. Specific examples of the at least one compound selected from the group consisting of proteins and peptides that can be suitably used include protamine (Pro), lysozyme (Lys), ribonuclease A (Rib), nisin (Nis), bone morphogenetic protein (BMP), basic fibroblast growth factor (FGF-2), transforming growth factor-β (TGF-β), and the like. The isoelectric point of proteins and peptides can be determined by referring to the value at the time of purchasing the reagent (the value published by the reagent manufacturer), but it can also be measured by two-dimensional electrophoresis. For identification of proteins and peptides, proteins and peptides are separated and extracted by two-dimensional electrophoresis, and if the accurate molecular weight can be determined by MALDI-TOF MS, they can be identified by searching the Mascot database. If the accurate molecular weight cannot be determined by MALDI-TOF MS, the protein or peptide is fragmented by trypsin digestion, and the molecular weight of the fragments is determined by MALDI-TOF MS and LC MS / MS, and the database Mascot is searched for identification.

[0018] 2. Manufacturing method of implant material 1 (1) Manufacturing method There is no particular limitation on the method for producing the implant material 1. A suitable example of the method for producing the implant material 1 will be described below. This manufacturing method uses a first liquid containing at least one compound selected from the group consisting of proteins and peptides, which has an isoelectric point of greater than 7 when dispersed in water, and a second liquid containing liposomes formed from phospholipids. Then, the substrate 3 is alternately immersed in the first liquid and the second liquid.

[0019] (2) Specific examples of manufacturing methods (2.1) Synthesis of liposomes containing phospholipids The liquid containing liposomes synthesized by the method exemplified below becomes the second liquid. Here, as an example of the method for synthesizing liposomes, a method for synthesizing phosphatidylserine liposomes (PSL) will be described.

[0020] (2.1.1) Reagents The following reagents are used, for example: ·PS (L-α-phosphatidyl-L-serine: Sigma-Aldrich) ·PC (L-α-phosphatidylcholine: Sigma-Aldrich) ·DSPE-MAL (Distearoyl N-(3-Maleimide-1-oxopropyl)-L-α-phosphatidylethanolamine, NOF Corp.) ·F-DHPE (1,2-Dihexadecanoyl-sn-Glycero-3-Phosphoethanolamine, N-(Fluorescein-5-Thiocarbamoyl)-1,2-Dihexadecanoyl-sn-Glycero-3-Phosphoethanolamine, Triethylammonium Salt: Invitrogen)

[0021] (2.1.2) Preparation of stock solutions Each reagent is dissolved in a chloroform / methanol mixed solvent (e.g., v / v=9 / 1) to a concentration of, for example, 10 mg / mL to prepare a stock solution. Each stock solution is stored at a low temperature (e.g., -30°C).

[0022] (2.1.3) Synthesis of PSL (phosphatidylserine liposome) PSL is prepared in two types, a non-crosslinked type and a crosslinked type. An example of the synthesis method for each type is described below.

[0023] (2.1.3.1) Method for preparing non-crosslinked phosphatidylserine liposomes (non-crosslinked PSL) The method for preparing non-crosslinked phosphatidylserine liposomes (non-crosslinked PSL) is as follows. Each solution is added to a glass bottle so that the molar ratio is PS / PC = 30 / 70, and the solution is left to stand at room temperature overnight to evaporate the organic solvent and form a film. Bis-Tris buffer solution (100 mM, pH 7.1) is added so that the liposome concentration becomes a predetermined concentration (e.g., 10 mg / mL), and liposomes are formed by ultrasonic treatment. The liposomes are filtered using polycarbonate membranes with pore sizes of 0.8 μm, 0.4 μm, and 0.2 μm. From the viewpoints of surface charge and ease of liposome formation, the molar ratio of PS:PC is preferably within the range of 10:90 to 70:30.

[0024] (2.1.3.2) Preparation method of cross-linked phosphatidylserine liposomes (cross-linked PSL) The method for preparing cross-linked phosphatidylserine liposomes (cross-linked PSL) is as follows. Add each solution to a glass bottle so that the molar ratio is PS / PC / DSPE-MAL = 30 / 20 / 50, leave it at room temperature overnight to evaporate the organic solvent and form a film. As with non-cross-linked liposomes, the liposomes are formed by ultrasonic treatment and filtered. Mix 420 μL of liposomes (10 mg / mL), 420 μL of calcium chloride (8 mM), and 16.8 μL of dithiothreitol (DTT, 73.5 mM), and leave it at room temperature for 30 minutes to form cross-linked liposomes. From the viewpoints of surface charge and ease of liposome formation, the molar ratio of PS:PC is preferably 40:60 to 90:10, and from the viewpoint of the degree of crosslinking, the molar ratio of the total of PS and PC (total of PS+PC):DSPE-MAL is preferably 30:70 to 70:30. Instead of DSPE-MAL having a maleimide group, a dialkyl compound having a maleimide group, in which the alkyl group (including unsaturation) has 10 to 22 carbon atoms, can be used. Hereinafter, these dialkyl compounds having a maleimide group are also referred to as "specific compounds". The specific compounds present in the liposomes are crosslinked with dithiothreitol (DTT) to form crosslinked phosphatidylserine liposomes. For example, at least one of the following specific compounds can be used. ·DSPE-MAL: Distearoyl N-(3-maleimido-1-oxopropyl)-L-α-phosphatidylethanolamine DMPE-MAL: Dimyristoyl N-(3-maleimido-1-oxopropyl)-L-α-phosphatidylethanolamine ·DPPE-MAL: Dipalmitoyl N-(3-maleimido-1-oxopropyl)-L-α-phosphatidylethanolamine POPE-MAL: 1-Paramytoyl-2-oleoyl N-(3-maleimido-1-oxopropyl)-L-α-phosphatidylethanolamine DOPE-MAL: Dioleoyl N-(3-maleimido-1-oxopropyl)-L-α-phosphatidylethanolamine When these specific compounds are used, the molar ratio of the total of PS and PC (total of PS+PC):specific compound is preferably 30:70 to 70:30 from the viewpoint of the degree of crosslinking.

[0025] (2.1.4) Method for forming the coating layer 5 (method for producing the implant material 1) The coating layer 5 is preferably formed by alternately immersing the substrate 3 in the first liquid and the second liquid. As the first liquid, an aqueous solution containing at least one compound selected from the group consisting of proteins and peptides, which has an isoelectric point of more than 7 when dispersed in water, is preferably used. In order to utilize electrostatic interactions, it is preferable to alternately immerse the substrate 3 in the second liquid, which is an aqueous solution containing an anionic PSL, and the first liquid, which is an aqueous solution containing a cationic polymer, to form a coating layer 5, which is a mixed layer containing PSL and a polymer, on the substrate 3. Note that the "cationic polymer" here refers to at least one compound selected from the group consisting of proteins and peptides, which has an isoelectric point of more than 7 when dispersed in water. In this method, since PSL is negatively charged in an aqueous solution and protein or peptide is positively charged in an aqueous solution, the two are electrostatically adsorbed and bonded. By alternately immersing in two types of liquid, the negatively charged PSL and the positively charged protein or peptide are stacked (laminated) alternately to form a coating layer 5. In order to utilize the electrostatic adsorption between the PSL and the protein or peptide in this way, the isoelectric point of the protein or peptide is preferably greater than 7 and less than 14 in pure water. If it is not greater than 7, electrostatic adsorption does not occur by alternate immersion, and a mixed layer is unlikely to be formed on the substrate 3. If the isoelectric point of the protein or peptide is 14 or more, even if negatively charged PSL is stacked on a positively charged protein or peptide, the surface of the PSL will be positively charged due to the influence of the positive charge of the protein or peptide present below the PSL. Then, a repulsive force is generated between the positively charged surface of the PSL and the positively charged protein or peptide, and further stacking is not possible, and there is a risk that a sufficient coating layer 5 will not be formed. Therefore, the isoelectric point of the protein or peptide is preferably less than 14.

[0026] (2.1.5) Specific examples of methods for forming the coating layer 5 The following is a more specific example of a method for forming the coating layer 5. In this example, a substrate 3 having a negatively charged surface is used. Prepare an aqueous solution of protein or peptide (first solution, concentration: 0.5 mg / mL to 2 mg / mL). Prepare an aqueous dispersion of non-crosslinked PSL or crosslinked PSL (second solution, concentration: 0.5 mg / mL - 2 mg / mL). Then, the following steps A1, B1, and C1 are carried out in this order, and then, as necessary, B1 and C1 are alternately repeated. That is, each step is carried out in the order of A1, B1, C1 (B1, C1, C1). A drying step may be carried out after the final step. [Step A1] The substrate 3 is allowed to stand in the first solution at a predetermined temperature (e.g., 1 to 40°C) for a predetermined time (e.g., 1 hour to 2 days) to adsorb proteins or peptides. Thereafter, the substrate 3 is immersed in water (e.g., ultrapure water) for a predetermined time (e.g., 30 seconds to 30 minutes) to remove unadsorbed proteins or peptides. [Step B1] The substrate 3 is allowed to stand in the second solution at a predetermined temperature (e.g., 1 to 40°C) for a predetermined time (e.g., 30 seconds to 30 minutes) to adsorb PSL. Thereafter, the substrate 3 is immersed in water (e.g., ultrapure water) for a predetermined time (e.g., 30 seconds to 30 minutes) to remove unadsorbed PSL. [Step C1] The substrate 3 is allowed to stand in the first solution at a predetermined temperature (e.g., 1 to 40° C.) for a predetermined time (e.g., 30 seconds to 30 minutes) to adsorb the protein or peptide. Thereafter, the substrate 3 is immersed in water (e.g., ultrapure water) for a predetermined time (e.g., 30 seconds to 30 minutes) to remove unadsorbed protein or peptide.

[0027] The following is another specific example of the method for forming the coating layer 5. In this example, a substrate 3 having a positively charged surface is used. Prepare an aqueous solution of protein or peptide (first solution, concentration: 0.5 mg / mL to 2 mg / mL). Prepare an aqueous dispersion of non-crosslinked PSL or crosslinked PSL (second solution, concentration: 0.5 mg / mL - 2 mg / mL). Then, the following [Step A2], [Step B2], and [Step C2] are carried out, and then, as necessary, [Step B2] and [Step C2] are repeated alternately. That is, each step is carried out in the order of [Step A2] → [Step B2] → [Step C2] (→ [Step B2] → [Step C2]...). Note that a drying step may be provided after the final step. [Step A2] The substrate 3 is allowed to stand in the second solution at a predetermined temperature (e.g., 1 to 40°C) for a predetermined time (e.g., 1 hour to 2 days) to adsorb PSL. Thereafter, the substrate 3 is immersed in water (e.g., ultrapure water) for a predetermined time (e.g., 30 seconds to 30 minutes) to remove unadsorbed PSL. [Step B2] The substrate 3 is allowed to stand in the first solution at a predetermined temperature (e.g., 1 to 40° C.) for a predetermined time (e.g., 30 seconds to 30 minutes) to adsorb the protein or peptide. Thereafter, the substrate 3 is immersed in water (e.g., ultrapure water) for a predetermined time (e.g., 30 seconds to 30 minutes) to remove unadsorbed protein or peptide. [Step C2] The substrate 3 is allowed to stand in the second solution at a predetermined temperature (e.g., 1 to 40° C.) for a predetermined time (e.g., 30 seconds to 30 minutes) to adsorb PSL. Thereafter, the substrate 3 is immersed in water (e.g., ultrapure water) for a predetermined time (e.g., 30 seconds to 30 minutes) to remove unadsorbed PSL.

[0028] If the surface of the base material 3 is not charged, a step of positively or negatively charging the surface may be provided before the alternate immersion. EXAMPLES

[0029] The present disclosure will now be described more specifically. 1. Experiment 1 (coating on titanium material) (1) Preparation of non-crosslinked phosphatidylserine liposomes (non-crosslinked PSL) containing fluorescent lipid F-DHPE Each solution was added to a glass bottle so that the molar ratio was PS / PC / F-DHPE = 29 / 68 / 3, and the solution was left at room temperature overnight to evaporate the organic solvent and form a film. A Bis-Tris buffer solution (100 mM, pH 7.1) was added so that the liposome concentration was the specified concentration (10 mg / mL), and liposomes were formed by ultrasonic treatment. The liposomes were filtered using polycarbonate membranes with pore sizes of 0.8 μm, 0.4 μm, and 0.2 μm.

[0030] (2) Preparation of cross-linked phosphatidylserine liposomes (cross-linked PSL) containing fluorescent lipid F-DHPE The method for preparing cross-linked phosphatidylserine liposomes (cross-linked PSL) is as follows. Each solution was added to a glass bottle so that the molar ratio was PS / PC / DSPE-MAL / F-DHPE = 29 / 20 / 49 / 3, and the solution was left at room temperature overnight to evaporate the organic solvent and form a film. As with the non-cross-linked liposomes, the solution was converted into liposomes by ultrasonic treatment and filtered. 420 μL of liposomes (10 mg / mL), 420 μL of calcium chloride (8 mM), and 16.8 μL of dithiothreitol (DTT, 73.5 mM) were mixed and left at room temperature for 30 minutes to form cross-linked liposomes.

[0031] (3) Base material (substrate) A plate (titanium material) of pure titanium (manufactured by Nilaco Corporation) was used as the substrate. The titanium material was subjected to surface plasma treatment for 30 minutes using a surface plasma treatment device. The conditions for the surface plasma treatment were a frequency of 50 kHz, power of 100 W, degree of vacuum of 0.05 T, and air flow rate of 10 sscm.

[0032] (4) Formation of the coating layer An aqueous solution of protamine (first solution, concentration: 1 mg / mL) was prepared. Salmon-derived protamine sulfate (isoelectric point: 10 to 12) from Sigma-Aldrich was used as the protamine. An aqueous dispersion of non-crosslinked PSL or crosslinked PSL (second solution, concentration: 1 mg / mL) was prepared, and the following steps [Step A1], [Step B1], and [Step C1] were carried out in this order. [Step A1] The substrate is left to stand in the first solution at a predetermined temperature (4°C) for a predetermined time (overnight) to adsorb protamine, and then the substrate is immersed in water (ultrapure water) for a predetermined time (1 minute) to remove unadsorbed protamine. [Step B1] The substrate is left in the second solution at room temperature (22 to 25°C) for a predetermined time (1 minute) to adsorb PSL, and then the substrate is immersed in water (ultrapure water) for a predetermined time (1 minute) to remove unadsorbed PSL. [Step C1] The substrate is left to stand in the first solution at room temperature (22 to 25°C) for a predetermined time (1 minute) to adsorb protamine, and then the substrate is immersed in water (ultrapure water) for a predetermined time (1 minute) to remove unadsorbed protamine. This series of operations was the first cycle. From the second cycle onwards, [Step B1] and [Step C1] were repeated as one cycle. That is, as described below, after the first cycle of [Step A1], [Step B1] and [Step C1], a set of [Step B1] and [Step C1] was repeated (prescribed cycle number - 1) times. After the final cycle, [Step A1] was repeated three times, and the substrate was dried by vacuum drying. 1st cycle: [Process A1] [Process B1] [Process C1] 2nd cycle: [Step B1] [Step C1] 3rd cycle: [Step B1] [Step C1] 4th cycle: [Step B1] [Step C1] .... nth cycle: [Step B1] [Step C1]

[0033] Using the above procedure, coating layers were prepared for non-crosslinked PSL and crosslinked PSL after 5, 10, and 30 cycles.

[0034] (5) Measurement method for the amount of PSL supported on the substrate and the measurement results (5.1) Method for measuring PSL amount The substrate with the coating layer was immersed in 2 mL of the third solution (2% Triton X-100, 2 M sodium chloride, 100 mM Tris-HCl, pH 7.5) and then shaken overnight at 200 rpm in the dark to release the fluorescent liposomes from the substrate. The fluorescence intensity of the solution was measured using a plate reader (excitation wavelength 485 nm, fluorescence wavelength 530 nm). The PSL concentration in the solution was determined from a calibration curve of PSL solutions of known concentrations, and the amount of PSL adsorbed to the substrate was calculated.

[0035] (5.2) Measurement results of the amount of PSL supported on the substrate The results are shown in the graph in Figure 2. After 30 cycles, the loading amount of non-crosslinked PSL was 16 μg / cm 2 The loading of cross-linked PSL was 136 μg / cm 2It was confirmed that the amount of PSL supported increased with an increase in the number of cycles for both non-crosslinked and crosslinked PSL. Since the amount supported is proportional to the number of cycles, it is clear that it is possible to further increase the amount supported than in this experiment.

[0036] (6) Anti-inflammatory test The anti-inflammatory properties of a substrate having a coating layer using cross-linked PSL were tested. The relationship between the number of cycles and the amount of inflammatory cytokine IL-6 was investigated. The amount of inflammatory cytokine IL-6 in the substrate made of pure titanium was set at 100% for the number of cycles of 0. The lower the amount of inflammatory cytokine IL-6, the better the anti-inflammatory properties. The results are shown in the graph in Figure 3. After five cycles, the coating layer had a concentration of 22 μg / cm 2 After 10 cycles, the coating layer contained 50 μg / cm 2 From the viewpoint of anti-inflammatory properties, the amount of PSL supported was 20 μg / cm 2 It is preferable that the concentration is 50 μg / cm or more. 2 More preferably, it is 130 μg / cm or more. 2 More preferably, it is equal to or greater than this.

[0037] 2. Experiment 2 (Coating on PEEK material, coating on collagen sheet material) (1) Preparation of cross-linked phosphatidylserine liposomes (cross-linked PSL) containing fluorescent lipid F-DHPE Cross-linked PSL was prepared as in Experiment 1. (2) Base material The substrates used were PEEK and collagen sheet materials. (3) Formation of the coating layer (3.1) In the case of PEEK material A plate-shaped PEEK material was subjected to surface plasma treatment using a surface plasma treatment device. The treatment was the same as for the titanium material in Experiment 1, except that the treatment time was 1 minute. The formation of the coating layer and the measurement of the amount of PSL were also carried out in the same manner as in Experiment 1. Note that crosslinked PSL was used in this experiment. (3.2) Collagen sheet material A covering layer was formed on the collagen sheet material. The formation of the coating layer and the measurement of the amount of PSL were carried out in the same manner as in Experiment 1. Note that crosslinked PSL was used in this experiment. (4) Results The relationship between the number of cycles and the amount of PSL supported on various substrates is shown in Figure 4. For reference, the case of the titanium material in Experiment 1 is also shown in Figure 4. As shown in Figure 4, the amount of PSL supported increased with an increase in the number of cycles for all substrates. In other words, the amount of PSL supported could be controlled by the number of cycles, regardless of the type of substrate.

[0038] 3. Experiment 3 (Formation of a coating layer using proteins or peptides with different isoelectric points) The following proteins or peptides were used: · Sigma-Aldrich salmon-derived protamine sulfate (isoelectric point: 10-12) ·Egg white lysozyme from Fujifilm Wako Co., Ltd. (isoelectric point: 10.7) Ribonuclease A from bovine pancreas (isoelectric point: 8.6) from Serva Electrophoresis GmbH Nisin from Lactobacillus lactis (Sigma-Aldrich) (isoelectric point: 8.3) Horse myoglobin (isoelectric point: 7.0) from Serva Electrophoresis GmbH

[0039] The isoelectric points shown here refer to the values ​​provided by the manufacturer when the reagents were purchased. A coating layer was formed on the PEEK material in the same manner as in Experiment 2. A cross-linked type PSL was used, and the immersion cycle was 30 cycles.

[0040] The experimental results are shown in Table 1. It was found that when the isoelectric point of the protein or peptide is greater than 7, a coating layer is easily formed.

[0041] [Table 1]

[0042] 4. Experiment 4 (Measurement of PSL loading amount in Experiment 3) In experiment 3, the amount of PSL supported on the substrate was measured in the same manner as in experiment 1. The results are shown in Figure 5. Nisin was 19 μg / cm 2 , ribonuclease A was 23 μg / cm 2 , lysozyme 40 μg / cm 2 , protamine 89 μg / cm 2 These proteins or peptides were sufficiently supported on the substrate.

[0043] 5. Experiment 5 (Relationship between PSL loading amount and tissue regeneration effect) (1) Bone regeneration using titanium materials Rats (12 weeks old) were anesthetized intraperitoneally, and the skin and muscles were incised to expose the femoral knee joint, creating a standardized full-thickness bone defect of approximately 1.5 mm in diameter. A titanium material with a diameter of 1.4 mm and a length of 23 mm, coated with a coating layer (30 cycles) containing cross-linked PSL prepared in Experiment 1, was then embedded in the defect. As a control, rats were prepared with untreated titanium materials embedded in them. After embedding the sample, the muscles and skin were sutured and the surgery was completed. The postoperative observation periods were 1 and 2 weeks, with n=4 for each period.

[0044] One and two weeks after surgery, the animals were sacrificed by overdose of anesthesia, and samples and surrounding tissues were collected and immersion-fixed in 0.1M phosphate-buffered 4% paraformaldehyde (pH 7.4). The excised specimens were decalcified with 10% EDTA, the titanium material was removed, and paraffin specimens were prepared. 6 μm-thick tissue sections were prepared and histologically examined using hematoxylin-eosin staining. Furthermore, the amount of newly formed bone within the created defects (newbone / mm2) was determined using tissue sections from the central area (multiple areas) of the defects in each specimen. 2) was histologically and quantitatively examined. The specimens were photographed using an upright microscope (BX43, Olympus), and the amount of new bone formed was calculated by image processing of the micrographs using image processing software (cellsens, Olympus). Analysis of variance and other tests were performed using the average and standard deviation of the new bone mass of each group to test for significance. The significance level was set at 5%.

[0045] The results are shown in Figure 6. Figure 6 shows the area of ​​new bone one week and two weeks after implantation of a titanium material (Ti-0) that was not coated with a coating layer containing cross-linked PSL, and a titanium material (Ti-30) that was coated with a coating layer containing cross-linked PSL by 30 cycles of alternating immersion. After two weeks, the titanium material (Ti-30) coated with a coating layer containing cross-linked PSL was found to have approximately twice as much new bone as the uncoated titanium material (Ti-0). This demonstrates that the titanium material (Ti-30) coated with a coating layer containing cross-linked PSL has a high bone regeneration ability.

[0046] (2) Muscle tissue regeneration using PEEK material Rats (12 weeks old) were anesthetized intraperitoneally, the skin of the thigh was incised, the thigh muscle was clearly exposed, and a cylindrical PEEK material with a diameter of 1 mm and a length of 10 mm, coated with a coating layer (30 cycles, 75 cycles) containing cross-linked PSL prepared in Experiment 2, was implanted into the muscle. An untreated PEEK material was also implanted as a control. After the sample was implanted, the skin was sutured and the surgery was completed. The postoperative observation periods were 2, 4, and 8 weeks, with n=6 for each period. Two, four and eight weeks after surgery, the animals were sacrificed by overdose of anesthesia, and samples and surrounding tissues were collected and immersion-fixed in 0.1M phosphate-buffered 4% paraformaldehyde (pH 7.4). The PEEK material was removed from the excised specimens, and paraffin specimens were prepared. 6μm-thick tissue sections were prepared and histologically examined using hematoxylin-eosin staining. Furthermore, the amount of regenerated muscle around the implanted PEEK material (regenerated muscle area / μm) was determined using tissue sections from the central defect area (multiple areas) of each specimen. 2) was histologically and quantitatively examined. The specimens were photographed using an upright microscope (BX43, Olympus), and the amount of regenerated muscle was calculated by processing the microscopic photographs with image processing software (cellsens, Olympus). Analysis of variance and other tests were performed using the average and standard deviation of the regenerated muscle mass of each group, and a significance test was performed. The significance level was set at 5%.

[0047] The area of ​​regenerated muscle tissue 2, 4, and 8 weeks after implantation for PEEK material not coated with a coating layer (PEEK-0) and PEEK materials coated with a coating layer by 30 and 75 cycles of alternating immersion (PEEK-30, PEEK-75) is shown in the graph in Figure 7. It was confirmed that PEEK materials coated with a coating layer containing cross-linked PSL by 30 or more cycles of alternating immersion (PEEK-30, PEEK-75) had higher bone regeneration ability than PEEK material not coated with a coating layer (PEEK-0).

[0048] 6. Effects of the embodiment The implant material of this embodiment contains a sufficient amount of phospholipids, and therefore has high bone regeneration and muscle tissue regeneration capabilities.

[0049] <Other embodiments (modifications)> The present invention is not limited to the above examples and embodiments, and can be embodied in various forms without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0050] 1. Implant material 3...Base material 5…Covering layer 7. Liposomes 9...At least one compound selected from the group consisting of proteins and peptides

Claims

1. An implant material comprising a substrate and a coating layer that coats a surface of the substrate, The coating layer is a crosslinked liposome formed by containing at least one type of phospholipid having an isoelectric point of less than 7 when dispersed in water; At least one compound selected from the group consisting of proteins and peptides having an isoelectric point of more than 7 when dispersed in water; An implant material comprising:

2. The implant material described in claim 1, wherein the crosslinked liposomes are crosslinked using dithiothreitol.

3. The implant material according to claim 1 , wherein the phospholipid is a glycerophospholipid.

4. An implant material as described in claim 1 or claim 2, wherein the crosslinked liposome is a crosslinked phosphatidylserine liposome.

5. The implant material according to claim 1 , wherein the coating layer contains protamine as the protein.

6. The implant material according to claim 1 , wherein the substrate is made of a metal, a polymer, or a composite thereof.

7. a first liquid containing at least one compound selected from the group consisting of proteins and peptides, the compound having an isoelectric point of greater than 7 when dispersed in water; a second liquid containing crosslinked liposomes formed by containing phospholipids; A method for producing an implant material, comprising at least a step of alternately immersing a substrate in the first liquid and the second liquid.

Citation Information

Patent Citations

  • Phospholipid-coated implants

    JP2003508129A